Confirmatory factor analysis of psychotic-like experiences in a general population sample. (30th January 2016) - Therman, Sebastian; Ziermans, Tim B.
Abstract: Psychotic-like experiences (PLEs) are sub-psychotic expressions of the psychosis continuum. Several studies have suggested multifactorial models, including a bifactor model, of the putative PLEs assessed with the popular Community Assessment of Psychic Experiences (CAPE) questionnaire. Our confirmatory results in a gender-balanced population of adolescents and young adults support a three-factor Paranoia–Delusions–Hallucinations structure of PLEs, which excludes Grandiosity and Common Paranormal Beliefs. The best latent models achieved excellent fit when taking the categorical nature of the responses into consideration. Highlights: Confirmatory factor analyses of the CAPE were applied in a population sample. The best previous exploratory models had excellent fit. Psychotic-like experiences had a Paranoia–Delusions–Hallucinations structure. Taking the categorical nature of the items into account significantly improved fit.